Income Inequality Rankings for Different Equivalence Scales and Population Health - José María Sarabia; Marta Pascual; David Cantarero (European Regional Science Association (ERSA), 2003)
This paper is divided in two parts. The first one is dedicated to analyse the inequality of the income distribution in Spain during the convergence process to the European Monetary Union. To carry out this task, we propose two robust models based on the quantile functions. Specifically, we use the Gamma and Beta quantile functions. The income inequality in Spain and the sensitivity of the results for different equivalence scales are analysed using the data corresponding to the first five waves (1994-1998) of the European Community Household Panel (ECHP). This survey contains data on individuals and households and the information is homogeneous across European countries. The second part of the paper is dedicated to study the correlation between income inequality and one of the most important health indicators such as life expectancy. We will try to add new perspectives to conventional studies of health inequalities. With this aim we will focus on relations between socio-economic factors and health of the individuals. In conclusion, this analysis seems to confirm the results obtained in previous researches. Income distribution has significant effects on health indicators. Although we can not confirm that the social capital is highly related with health, at least it is an important factor which helps to explain it. Key words: Inequality, social capital, health, European Community Household Panel
Keywords: 330